Fertility rates and perinatal outcomes of adolescent pregnancies: a retrospective population-based study - Maria de Lourdes de Souza; Fiona Ann Lynn; Linda Johnston; Eduardo Cardoso Teixeira Tavares; Odaléa Maria Brüggemann; Lúcio José Botelho
ABSTRACT Objective: analyze trends in fertility rates and associations with perinatal outcomes for adolescents in Santa Catarina, Brazil. Methods: a population-based study covering 2006 to 2013 was carried out to evaluate associations between perinatal outcomes and age groups, using odds ratios, and Chi-squared tests. Results: differences in the fertility rate among female adolescents across regions and time period were observed, ranging from 40.9 to 72.0 per 1,000 in mothers aged 15-19 years. Adolescents had fewer prenatal care appointments than mothers ≥20 years, and a higher proportion had no partner. Mothers aged 15-19 years were more likely to experience preterm birth (OR:1.1; CI:1.08-1.13; p<0.001), have an infant with low birthweight (OR:1.1; CI:1.10-1.15; p<0.001) and low Apgar score at 5 minutes (OR:1.4; CI:1.34-1.45; p<0.001) than mothers ≥20 years, with the odds for adverse outcomes greater for those aged 10-14 years. Conclusion: this study provides evidence of fertility rates among adolescents remaining higher in regions of social and economic deprivation. Adolescent mothers and their infants more likely to experience adverse perinatal outcomes. Nurses, public health practitioners, health and social care professionals and educators need to work collaboratively to better target strategies for adolescents at greater risk; to help reduce fertility rates and improve outcomes.